Involvement of T Cell Immunity in Avian Coccidiosis - Kim, Woo H.; Chaudhari, Atul A.; Lillehoj, Hyun S. (Frontiers in Immunology, 2019)
Avian coccidiosis is caused by Eimeria, which is an intracellular apicomplexan parasite that invades through the intestinal tract to cause devastating disease. Upon invasion through the intestinal epithelial cells, a strong inflammatory response is induced that results in complete villous destruction, diarrhea, hemorrhage, and in severe cases, death. Since the life cycle of Eimeria parasites is complex and comprises several intra- and extracellular developmental stages, the host immune responses are diverse and complex. Interferon-γ-mediated T helper (Th)1 response was originally considered to be the predominant immune response in avian coccidiosis. However, recent studies on other avian T cell lineages such as Th17 and T regulatory cells have implicated their significant involvement in maintaining gut homeostasis in normal and disease states including coccidiosis. Therefore, there is a need to understand better their role in coccidiosis. This review focuses on research findings concerning the host immune response induced by avian coccidiosis in the context of T cell immunity, including expression of T-cell-related cytokines and surface molecules that determine the phenotype of T lymphocytes.